Privatisation of government owned banks and the issue of ownership and control : legal and economic perspectives - Ayua, I. A.; Owasanoye, Bolaji; Nigerian Institute of Advanced Legal Studies (Lagos : Nigerian Institute of Advanced Legal Studies, 1996)
Papers and proceedings of a one-day roundtable conference convened by Department of Commercial and Property Law, Nigerian Institute of Advanced Legal Studies, University of Lagos Campus, Akoka
"Papers and proceedings of a one-day roundtable conference convened by Department of Commercial and Property Law, Nigerian Institute of Advanced Legal Studies, University of Lagos Campus, Akoka."
Includes bibliographical references
oif 28/01/2019
Loans
Keywords: Banks and banking -- Government ownership -- Congresses; Privatization -- Nigeria -- Congresses; Banks and banking -- Government ownership; Privatization; Nigeria